2019
DOI: 10.1103/physrevb.99.045113
|View full text |Cite
|
Sign up to set email alerts
|

Orbital-selective confinement effect of Ru 4d orbitals in SrRuO3 ultrathin film

Abstract: The electronic structure of SrRuO3 thin film with thickness from 50 to 1 unit cell (u.c.) is investigated via the resonant inelastic x-ray scattering (RIXS) technique at the O K-edge to unravel the intriguing interplay of orbital and charge degrees of freedom. We found that orbital-selective quantum confinement effect (QCE) induces the splitting of Ru 4d orbitals. At the same time, we observed a clear suppression of the electron-hole continuum across the metal-to-insulator transition (MIT) occurring at the 4 u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Previous work has shown that meaningful insight regarding OER activity can be drawn from ex-situ O K-edge measurements of asprepared materials, even though the surface under reaction conditions may differ. 21,46 The two pre-edge features in the O K-edge spectra at ∼529 eV and 532 eV represent the transition of a core O 1s electron to Ru 4d t 2g and e g states that hybridize with O 2p states, respectively 22,47,48 (Figure 1E). These pre-edge features have previously been used to estimate the extent of hybridization between the O 2p and Ru 4d orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that meaningful insight regarding OER activity can be drawn from ex-situ O K-edge measurements of asprepared materials, even though the surface under reaction conditions may differ. 21,46 The two pre-edge features in the O K-edge spectra at ∼529 eV and 532 eV represent the transition of a core O 1s electron to Ru 4d t 2g and e g states that hybridize with O 2p states, respectively 22,47,48 (Figure 1E). These pre-edge features have previously been used to estimate the extent of hybridization between the O 2p and Ru 4d orbitals.…”
Section: Resultsmentioning
confidence: 99%
“…On a microscopic level, they are governed by a number of transition metal d electrons, the strength of spin-orbit coupling, the strength of correlation effects, the Hund's rule coupling, and the ionic radii of the A-site element [5,6]. As the relevant energy scales of these factors become more comparable to one another for 4d orbitals, the ground state of 4d transition metal oxides, in particular of ruthenates, becomes more sensitive to perturbation with the particular importance of the orbital degree of freedom [3,4,7]. One should also note that Ru has a moderate spin-orbit interaction of 75 meV as compared with its 5d counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal oxides (TMOs) with strong delectron correlations and spin-orbit coupling (SOC) may provide an effective platform towards emergent magnetism with controllable spin textures [12][13][14][15][16][17][18][19][20]. SrRuO3 (SRO) is a unique 4d TMO with a coexistence of SOC and itinerant ferromagnetism [21], leading to a large variety of physical behaviors which have been experimentally observed such as high-spin states driven by crystal orientations [22][23][24], magnetic skyrmions due to the broken symmetry [25][26][27][28], and metal-insulator transition [29][30][31], etc. More importantly, emergent physical behaviors have been theoretically proposed in SRO recently [13,15,32,33], triggering a broad attention to discover the potential quantum states in this material.…”
mentioning
confidence: 99%